Composition, richness and nestedness of gallery forest bird assemblages in an Amazonian savanna landscape: lessons for conservation - Joandro Pandilha; José Júlio de Toledo; Luis Cláudio Fernandes Barbosa; William Douglas Carvalho; Jackson Cleiton de Sousa; José Maria Cardoso da Silva (PeerJ, 2021)
Gallery forests are important to the maintenance of a substantial portion of the biodiversity in neotropical savanna regions, but management guidelines specific to this forest type are limited. Here, we use birds as study group to assess if: (1) functional traits can predict the abundance and occupancy of forest species within a savanna landscape, (2) habitat structures influence the taxonomic, functional, and phylogenetic diversity of forest assemblages, and (3) less diverse gallery forest assemblages are a nested subset of more diverse assemblages living near continuous forests. Then, we propose strategies on how gallery forests can be managed to maintain their species assemblages amidst the fast expansion of human activities across tropical savanna landscapes. We studied 26 sites of gallery forests in an Amazonian savanna landscape and found that: (1) habitat specificity is the only functional trait that predicts species abundance and occupancy across a landscape; (2) phylogenetic diversity is negatively correlated with understory foliage density; (3) the percentage of forests and savannas around sites is positively correlated with both phylogenetic and functional diversity; (4) increasing human activities around gallery forest negatively influences taxonomic and functional diversity; and (5) forest bird assemblages are not distributed at random across the landscape but show a nested pattern caused by selective colonization mediated by habitat filtering. Our combined findings have three implications for the design of conservation strategies for gallery forest bird assemblages. First, maintaining the connectivity between gallery forests and adjacent continuous forests is essential because gallery forest bird assemblages are derived from continuous forest species assemblages. Second, because most species use the savanna matrix to move across the landscape, effectively managing the savanna matrices where gallery forests are embedded is as important to maintaining viable populations of forest bird species as managing the gallery forest themselves. Third, in savanna landscapes planned to be used for agriculture production, protecting gallery forests alone is not enough. Instead, gallery forests should be protected with surrounding savanna buffers to avoid the detrimental effects (edge effects and isolation) of human activities on their biodiversity.